Hot melt adhesive, preparation method thereof, gummed paper, wound battery cell, battery and electric equipment
By using polyolefins, maleic anhydride-containing polymers, toughener and adhesive-enhancing glue in the wound cell, the problem of pole cracking is solved, and the electrolyte resistance and life of the cell is improved. Ensure the battery cell is operating normally.
Patent Information
- Application Number
- CN202310753375.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
AI Technical Summary
In actual production and application of winding battery cells, excessive stress in some arc-shaped areas causes the pole sheet to crack, affecting the life and normal operation of the battery cells.
A hot melt adhesive including polyolefin, maleic anhydride-containing polymer, toughener and adhesive glue is used. The dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 8% to buffer the stress of the electrode sheet. , improve the electrolyte resistance performance and swell in the electrolyte to keep the battery cell running normally.
Effectively reduce the cracking problem of the electrode sheet, improve the life of the battery cell and the electrolyte resistance performance, and ensure that the battery cell does not affect the conductivity of the electrolyte and the adhesion of the electrode sheet during the charge and discharge cycle.
Smart Images

Figure CN119193040A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to hot melt adhesive and a preparation method thereof, adhesive tape, wound battery cells, batteries and electrical equipment. Background Art
[0002] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal, wind and solar power stations, but are also widely used in electric transportation vehicles such as electric bicycles, electric motorcycles, electric cars, as well as in military equipment, aerospace and other fields.
[0003] The wound battery cell is a widely used battery cell for secondary batteries. It is made by rolling together the positive electrode sheet, the negative electrode sheet and the isolation film. Therefore, the wound battery cell has an arc area. In actual production and application, some arc areas will be subjected to excessive force, resulting in cracking of the electrode sheet. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a hot melt adhesive that can reduce the problem of cracking of pole pieces.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a hot melt adhesive, comprising: polyolefin, a polymer containing maleic anhydride, a toughening agent and a tackifying adhesive, wherein the dissolution rate of the hot melt adhesive in an organic solvent is less than or equal to 8%.
[0006] The present application includes at least the following beneficial effects: the hot melt adhesive composed of the present application, when used in winding battery cells, can reduce the problem of cracking of the pole pieces and will not affect the normal operation of the battery cells.
[0007] In some embodiments of the present application, the hot melt adhesive comprises 10-60 parts by weight of polyolefin, 20-50 parts by weight of polymer containing maleic anhydride, 20-50 parts by weight of toughening agent and 1-10 parts by weight of tackifying adhesive. Alternatively, the hot melt adhesive comprises 10-40 parts by weight of polyolefin, 30-40 parts by weight of polymer containing maleic anhydride, 30-40 parts by weight of toughening agent and 1-5 parts by weight of tackifying adhesive. The hot melt adhesive composed above can play a buffering role and well improve the problem of cracking of the pole piece.
[0008] In some embodiments of the present application, the dissolution rate of the hot melt adhesive in the organic solvent is 4%-7%, and can be 5%-6%. Thus, the electrolyte resistance of the hot melt adhesive can be improved, and it can play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0009] In some embodiments of the present application, the solubility parameter of the polyolefin is 9 cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 , optional 10cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 Therefore, the low solubility of polyolefin in the electrolyte can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0010] In some embodiments of the present application, the weight average molecular weight of the polyolefin is 100,000-400,000, and can be 200,000-300,000. Thus, the electrolyte resistance of the hot melt adhesive can be improved, and it can play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0011] In some embodiments of the present application, the melting point of the polyolefin is 140° C.-160° C., and can be 145° C.-155° C. Thus, the polyolefin can have a certain flexibility, and the wetting ability of the electrolyte in the hot melt adhesive molecular chain can be improved.
[0012] In some embodiments of the present application, the crystallinity of the polyolefin is 1%-30%, and can be optionally 10%-20%. Within the above crystallinity range, the electrolyte resistance of the hot melt adhesive can be improved, and it can play a good buffering role and reduce the cracking of the electrode without affecting the normal operation of the battery cell.
[0013] In some embodiments of the present application, the polyolefin includes at least one of polypropylene, cycloolefin polymer and hexene-octene copolymer. The above polyolefin has strong electrolyte resistance, which can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0014] In some embodiments of the present application, the weight average molecular weight of the polymer containing maleic anhydride is 50,000-400,000, and can be 100,000-200,000. The polymer containing maleic anhydride can enhance the adhesion of the hot melt adhesive and improve the fluidity of the hot melt adhesive. Within the above weight average molecular weight range, the adhesion and buffering properties of the hot melt adhesive can be improved, and the normal operation of the battery cell can be not affected. It plays a good buffering role and reduces the cracking of the pole piece.
[0015] In some embodiments of the present application, the glass transition temperature of the polymer containing maleic anhydride is 50° C.-100° C., and can be 50° C.-70° C. Thus, the flexibility of the polymer containing maleic anhydride can be improved, and the adhesion of the hot melt adhesive can be improved.
[0016] In some embodiments of the present application, the maleic anhydride-containing polymer includes at least one of a maleic anhydride-containing butene-ethylene copolymer and a maleic anhydride-containing butene-octene copolymer. The maleic anhydride-containing polymer can enhance the adhesion of the hot melt adhesive, improve the fluidity of the hot melt adhesive, and improve the adhesion and buffering properties of the hot melt adhesive. It plays a good buffering role and reduces the cracking of the pole piece without affecting the normal operation of the battery cell.
[0017] In some embodiments of the present application, the weight average molecular weight of the toughening agent is 100,000-500,000, and can be 200,000-300,000. The toughening agent within the above weight average molecular weight range enables the hot melt adhesive to swell after being soaked in the electrolyte, which will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive, and play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0018] In some embodiments of the present application, the glass transition temperature of the toughening agent is -50°C-50°C, and can be -20°C-50°C. In this way, the flexibility of the toughening agent can be improved, and the adhesion of the hot melt adhesive can be improved.
[0019] In some embodiments of the present application, the branching degree of the toughening agent is 500-800, and can be 500-700. The branching degree of the toughening agent is within the above range, and it can swell after being immersed in the electrolyte, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains, which will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive, and play a good buffering role without affecting the normal operation of the battery cell, thereby reducing the cracking of the pole piece.
[0020] In some embodiments of the present application, the toughening agent includes at least one of styrene-isoprene-styrene triblock copolymer, styrene-butylene-styrene triblock copolymer and styrene-1-hexene-styrene triblock copolymer. The hot melt adhesive containing the above toughening agent will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive, and play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0021] In some embodiments of the present application, the weight average molecular weight of the tackifier is 10,000-100,000, and can be 20,000-50,000. Within the above weight average molecular weight range, the tackifier will not affect the operation of the battery cell, and can increase the viscosity of the hot melt adhesive, and play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0022] In some embodiments of the present application, the glass transition temperature of the tackifier is 50° C.-90° C., and can be 60° C.-70° C. Thus, the flexibility and viscosity of the tackifier can be improved, and the bonding property of the hot melt adhesive can be improved.
[0023] In some embodiments of the present application, the tackifier includes at least one of polyisobutylene, polyisoprene and butyl rubber. Thus, the tackifier can increase the viscosity of the hot melt adhesive and improve the bonding force between the hot melt adhesive and the pole piece.
[0024] In some embodiments of the present application, the hot melt adhesive further comprises 0.1 to 1 parts by weight of an additive. Optionally, the hot melt adhesive further comprises 0.1 to 0.5 parts by weight of an additive.
[0025] In some embodiments of the present application, the additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol and pentaerythritol tetrakis (3-laurylthiopropionate). Thus, the anti-oxidation performance of the hot melt adhesive can be improved.
[0026] The second aspect of the present application provides a method for preparing a hot melt adhesive, comprising: mixing a polyolefin, a polymer containing maleic anhydride, a toughening agent and a tackifying adhesive to obtain a hot melt adhesive, wherein the solubility rate of the hot melt adhesive in an organic solvent is less than or equal to 8%.
[0027] Therefore, the hot melt adhesive prepared by the method has good electrolyte resistance and good adhesion to the electrode. When the hot melt adhesive is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.
[0028] The third aspect of the present application provides an adhesive tape, comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in the first aspect of the present application or the hot melt adhesive prepared by the method described in the second aspect of the present application.
[0029] In some embodiments of the present application, the adhesive tape satisfies at least one of the following conditions:
[0030] The thickness ratio of the adhesive layer to the substrate is (5-8):(9-13), and can be optionally (7-8):(11-13);
[0031] The thickness of the adhesive tape is 16 μm-20 μm, and can be optionally 16 μm-18 μm.
[0032] The adhesive tape meets at least one of the above conditions. When used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can well improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.
[0033] The fourth aspect of the present application provides a wound battery cell, comprising a positive electrode sheet, a separator and a negative electrode sheet stacked and wound in sequence, and the adhesive tape described in the third aspect of the present application is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator.
[0034] Adhesive paper is arranged between the positive electrode plate and the isolation membrane and / or between the negative electrode plate and the isolation membrane. The hot melt adhesive has good electrolyte resistance and good bonding performance with the electrode plate. The hot melt adhesive plays a buffering role when the electrode plate is subjected to pressure, which can greatly improve the problem of electrode plate cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.
[0035] In some embodiments of the present application, the positive electrode sheet includes alternately arranged flat sections and bent sections, and the adhesive tape is provided on at least one side of the bent section. Therefore, the bent section has an arc-shaped area, which is subjected to large forces. Providing adhesive tape on at least one side of the bent section can well improve the problem of cracking of the electrode sheet, increase the life of the battery cell, and will not affect the normal operation of the battery cell.
[0036] In some embodiments of the present application, the adhesive tape is provided on at least one side of the bending section near the center of the wound battery cell. Therefore, the bending section near the center of the wound battery cell is subjected to large force and is prone to cracking. The adhesive tape is provided on at least one side of the bending section near the center of the wound battery cell, which can improve the problem of cracking of the pole piece and increase the life of the battery cell, and will not affect the energy density of the battery cell due to too much adhesive tape.
[0037] The fifth aspect of the present application provides a battery, comprising the wound battery cell described in the fourth aspect of the present application, so that the battery has a longer life.
[0038] The sixth aspect of the present application provides an electrical device, comprising the battery described in the fifth aspect of the present application. Thus, the electrical device has a longer lifespan.
[0039] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0041] Figure 1 It is a structural schematic diagram of a wound battery cell from one perspective of an embodiment of the present application;
[0042] Figure 2yes Figure 1 A schematic diagram of a portion of the structure of the middle positive electrode sheet in an unfolded state;
[0043] Figure 3 is a schematic structural diagram of a battery according to one embodiment of the present application;
[0044] Figure 4 is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0045] Figure 5 is a schematic structural diagram of a battery pack according to an embodiment of the present application;
[0046] Figure 6 yes Figure 5 Exploded diagram of
[0047] Figure 7 It is a schematic diagram of an embodiment of an electric device in which a battery is used as a power source.
[0048] Description of reference numerals:
[0049] 10: wound battery cell; 101: negative electrode sheet; 102: positive electrode sheet; 103: isolation film; 102-1: bent section of positive electrode sheet; 101-1: bent section of negative electrode sheet; 106: adhesive tape; 102-2: flat section of positive electrode sheet; 1: secondary battery; 2: battery module; 3: battery pack; 4: upper box; 5: lower box. DETAILED DESCRIPTION
[0050] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0051] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0052] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0053] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0055] At present, from the perspective of market development, the application of secondary batteries is becoming more and more extensive. Secondary batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of secondary batteries, the market demand is also constantly expanding.
[0056] The wound battery cell is a widely used battery cell for secondary batteries. It is made by rolling together the positive electrode sheet, the negative electrode sheet and the separator. Therefore, the wound battery cell has an arc area. In actual production and application, some areas will be subjected to excessive force, resulting in cracking of the electrode sheet. This problem will cause lithium deposition in the battery cell during the cycle process. As time goes on, the deposited lithium slowly turns into lithium dendrites, which pierce the separator and cause a short circuit inside the battery cell.
[0057] In order to reduce the stress on the pole piece, hot melt adhesive can be set on one side of the pole piece, and the hot melt adhesive plays a buffering role. However, due to the presence of a large amount of organic solvents in the electrolyte, the existing hot melt adhesive is easily dissolved into the electrolyte when used for the pole piece. On the one hand, the hot melt adhesive cannot play a buffering role. On the other hand, after the hot melt adhesive is dissolved in the electrolyte, it will increase the viscosity of the electrolyte and reduce the ionic conductivity of the electrolyte, thereby affecting the transmission of active ions in the electrolyte. In addition, after the hot melt adhesive is dissolved in the electrolyte, it will enter the positive and negative pole pieces with the charge and discharge cycle of the wound battery cell, deteriorating the electrodes.
[0058] When the hot melt adhesive of the present application is used for the pole piece of a wound battery cell, the hot melt adhesive plays a buffering role when the pole piece is subjected to pressure, which can greatly improve the problem of pole piece cracking and increase the life of the battery cell. In addition, the dissolution rate of the hot melt adhesive in organic solvents is less than or equal to 8%, the dissolution rate of the hot melt adhesive in the electrolyte is low, and the electrolyte resistance is good. The hot melt adhesive swells after being soaked in the electrolyte, which increases the spacing between the hot melt adhesive molecular chains, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains. In other words, the hot melt adhesive will not affect the normal operation of the wound battery cell, and can play a buffering role and improve the cracking of the pole piece.
[0059] The hot melt adhesive disclosed in the embodiment of the present application can be used for batteries, and the batteries disclosed in the embodiment of the present application can be used for electrical equipment using batteries as power sources or various energy storage systems using batteries as energy storage elements. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0060] In a first aspect, the present application provides a hot melt adhesive, comprising polyolefin, a polymer containing maleic anhydride, a toughening agent and a tackifying adhesive, wherein the dissolution rate of the hot melt adhesive in an organic solvent is less than or equal to 8%.
[0061] The present application includes at least the following beneficial effects: when the hot melt adhesive proposed in the present application is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can well improve the problem of cracking of the electrode and increase the life of the battery cell; in addition, the dissolution rate of the hot melt adhesive in the electrolyte is low, so that the hot melt adhesive has good electrolyte resistance, and the hot melt adhesive is not easy to increase the viscosity of the electrolyte in the electrolyte, which reduces the deterioration of the conductivity of the electrolyte by the hot melt adhesive, and at the same time reduces the deterioration of the electrode by the hot melt adhesive dissolved in the electrolyte; the hot melt adhesive swells after being immersed in the electrolyte, so that the spacing between the hot melt adhesive molecular chains increases, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains. In summary, the hot melt adhesive proposed in the present application, the four components work together, so that the hot melt adhesive has a low dissolution rate in the electrolyte and can swell in the electrolyte. When the hot melt adhesive is used to wind the battery cell, it can reduce the problem of cracking of the electrode and will not affect the normal operation of the battery cell.
[0062] The dissolution rate refers to the ratio of the mass of hot melt adhesive dissolved in an organic solvent to the initial mass of the hot melt adhesive. The method for determining the dissolution rate of hot melt adhesive in an organic solvent is as follows:
[0063] 1) Weigh a certain mass of hot melt adhesive, record it as M1
[0064] 2) Immersed in an electrolyte at 70°C for 5 hours, wherein the electrolyte comprises ethylene carbonate (EC), ethyl methyl carbonate (EMC) and electrolyte salt LiPF6, wherein the mass ratio of EC to EMC is 30:70 and the molar concentration of the electrolyte salt is 1.0 mol / L;
[0065] 3) Take out the hot melt adhesive and wipe the surface of the hot melt adhesive dry with dust-free paper;
[0066] 4) Immerse the hot melt adhesive in dimethyl carbonate (DMC) at 70°C for 24 hours;
[0067] 5) Take out the hot melt adhesive and wipe the surface of the hot melt adhesive dry with dust-free paper;
[0068] 6) Place the hot melt adhesive in an oven and dry at 90°C for 24 hours;
[0069] 7) Take out the membrane and weigh it, record it as M2
[0070] 8) Calculate the dissolution rate = (M1-M2) x 100% / M1.
[0071] Therefore, the dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 8%. For example, the dissolution rate of the hot melt adhesive in the organic solvent can be 1%-7.5%, 4%-7.5%, 4.5%-7%, 5%-6.5%, 5.5%-6%, etc. Specifically, the dissolution rate of the hot melt adhesive in the organic solvent is within the above range, which can improve the electrolyte resistance of the hot melt adhesive, reduce the increase of electrolyte viscosity caused by the dissolution of the hot melt adhesive in the electrolyte, and deteriorate the conductivity of the electrolyte to hinder the transmission of active ions. At the same time, it reduces the deterioration of the electrode caused by the dissolution of the hot melt adhesive in the electrolyte, and plays a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the electrode. In other embodiments of the present application, the dissolution rate of the hot melt adhesive in the organic solvent is 4%-7%, for example, 5%-6%.
[0072] In some embodiments of the present application, the organic solvent includes an organic solvent in the electrolyte. As an example, the organic solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0073] In some embodiments of the present application, the solubility parameter of the polyolefin is 9 cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 For example, the solubility parameter of polyolefins can be 9 cal 1 / 2 / cm 3 / 2 -10.8cal 1 / 2 / cm 3 / 2 , 9.2cal 1 / 2 / cm 3 / 2 -10.5cal 1 / 2 / cm 3 / 2 , 9.5cal 1 / 2 / cm 3 / 2 -10.1cal 1 / 2 / cm 3 / 2 , 9.8cal 1 / 2 / cm 3 / 2 -10cal 1 / 2 / cm 3 / 2 The solubility parameter range of the above polyolefin is greatly different from that of the electrolyte. The dissolution rate of the hot melt adhesive in the electrolyte is low, which makes the hot melt adhesive have good electrolyte resistance. The hot melt adhesive is not easy to increase the viscosity of the electrolyte in the electrolyte, which reduces the deterioration of the conductivity of the electrolyte by the hot melt adhesive. At the same time, it reduces the deterioration of the electrode by the hot melt adhesive dissolved in the electrolyte. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the electrode. In other embodiments of the present application, the solubility parameter of the polyolefin is 10cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 .
[0074] The solubility parameter is a parameter that characterizes the polymer-solvent interaction. When the solubility parameters of two materials are similar, they can be blended with each other and have good compatibility. In the examples of the present application, the solubility parameter determination method of the polyolefin is as follows:
[0075] (1) Selection of solvent and precipitant: First determine the solubility parameter δ of polyolefin p Range: Take a small amount of sample and do dissolution test in solvents with different solubility parameters (δ). If it is insoluble or dissolves slowly at room temperature, the polyolefin and solvent can be heated together and the hot solution can be cooled to room temperature. It is considered soluble only when no precipitation occurs. Select the appropriate solvent and precipitant.
[0076] (2) Prepare polymer solution according to the selected solvent: Weigh about 0.2 g of polyolefin sample and dissolve it in 25 ml of solvent (chloroform is used as solvent). Use a pipette to draw 5 ml (or 10 ml) of solution and place it in a test tube. Titrate the polymer solution with n-pentane first to produce a precipitate. Shake the test tube to dissolve the precipitate. Continue to drip n-pentane. The precipitate gradually becomes difficult to dissolve by shaking. Titrate until the precipitate that appears is just insoluble, and record the volume of n-pentane used. Titrate with methanol again, and operate the same as n-pentane, and record the volume of methanol used.
[0077] (3) Weigh 0.1 g and 0.05 g of the above polyolefin sample respectively, dissolve them in 25 ml of solvent, and titrate them in the same manner as above.
[0078] According to formula (1), the solubility parameter δ of the mixture is calculated mh and δ ml
[0079]
[0080] Where: and denote the volumes of n-pentane and methanol, respectively; δ1 and δ2 denote the solubility parameters of n-pentane and methanol, respectively.
[0081] The solubility parameter of polyolefin is calculated by formula (2).
[0082] δ p =1 / 2(δ mh +δ ml ) (2)
[0083] In some embodiments of the present application, the hot melt adhesive includes 10-60 parts by weight of polyolefin. For example, the hot melt adhesive includes 10-55 parts by weight of polyolefin, 15-50 parts by weight of polyolefin, 20-45 parts by weight of polyolefin, 25-40 parts by weight of polyolefin, 30-35 parts by weight of polyolefin, etc. Therefore, the use of polyolefin in the content of the present application can improve the electrolyte resistance of the hot melt adhesive, reduce the deterioration of the electrode caused by the hot melt adhesive dissolving in the electrolyte, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. In other embodiments of the present application, the hot melt adhesive of the present application includes 10-40 parts by weight of polyolefin.
[0084] In some embodiments of the present application, the weight average molecular weight of the polyolefin in the hot melt adhesive is 100,000-400,000. For example, the weight average molecular weight of the polyolefin can be 100,000-350,000, 150,000-300,000, 200,000-250,000, etc. Therefore, the use of polyolefins that meet the weight average molecular weight of this application can improve the electrolyte resistance of the hot melt adhesive and the adhesion to the pole piece, reduce the shedding of the hot melt adhesive during the battery cycle, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. In other embodiments of the present application, the weight average molecular weight of the polyolefin is 200,000-300,000.
[0085] The weight average molecular weight of the polyolefin can be measured by methods commonly used in the art, such as light scattering, ultracentrifugal sedimentation velocity, and gel chromatography.
[0086] The method for determining the weight average molecular weight of other substances hereinafter is the same as above.
[0087] In some embodiments of the present application, the melting point of the polyolefin is 140°C-160°C. For example, the glass transition temperature of the polyolefin may be 140°C-158°C, 143°C-155°C, 140°C-150°C, 143°C-145°C, etc. Therefore, the melting point of the polyolefin is within the above range, which can improve the flexibility of the hot melt adhesive and the adhesion to the pole piece, reduce the probability of the hot melt adhesive separating from the pole piece, and improve the wetting ability of the electrolyte in the hot melt adhesive molecular chain. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the melting point of the polyolefin is 140°C-150°C.
[0088] In the present application, the test method of the melting point of the polyolefin can be measured by the method commonly used in the art, for example, it can be measured by a microscopic melting point tester: the polymer sample is placed at the center of the hot plate surface, covered with insulating glass to form an insulating closed cavity, and the hot plate is heated at a certain speed. When the temperature reaches the melting point of the polymer, it can be clearly seen under a microscope that the transparency of a certain part of the polymer sample increases significantly and gradually extends to the entire sample. The temperature of the hot plate is displayed by a glass mercury thermometer. At the moment when the sample melts, the temperature at this time is immediately read on the thermometer, which is the melting point of the sample.
[0089] The melting points of other substances are determined in the same manner as above.
[0090] In some embodiments of the present application, the crystallinity of the polyolefin is 1%-30%. For example, the crystallinity of the polyolefin can be 5%-28%, 7%-25%, 10%-23%, 15%-20%, etc. Within the above crystallinity range, the electrolyte resistance of the hot melt adhesive can be improved and the service life of the electrode can be improved. In other embodiments of the present application, the crystallinity of the polyolefin is 10%-20%.
[0091] In the present application, the crystallinity test method of polyolefin can be measured by the method commonly used in the art, for example, by DSC determination: using Mettler Toledo82le DSC test, about 10 mg of sample is heated to 180°C at 10°C / min, kept at constant temperature for 2 minutes, and then cooled to 80°C at 10°C / min. The crystallinity obtained by DSC method can be calculated by the following formula:
[0092] X cd =ΔH m / ΔH m 0 ,
[0093] Where ΔH m and ΔH m 0 are the melting heat of the sample and the melting heat of the fully crystallized sample, respectively.
[0094] In some embodiments of the present application, the polyolefin includes at least one of polypropylene, cycloolefin polymer and hexene-octene copolymer. The above polyolefin has strong electrolyte resistance, which can improve the electrolyte resistance of the hot melt adhesive, play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0095] In some embodiments of the present application, the polyolefin also includes modified polyolefin formed by physical or chemical modification.
[0096] In some embodiments of the present application, the hot melt adhesive includes 20-50 parts by weight of a polymer containing maleic anhydride, for example, including 20-45 parts by weight of a polymer containing maleic anhydride, 25-40 parts by weight of a polymer containing maleic anhydride, 30-35 parts by weight of a polymer containing maleic anhydride, etc. Thus, by using the polymer containing maleic anhydride of the content of the present application, the polar group maleic anhydride can enhance the adhesion of the hot melt adhesive to the pole piece, and can also improve the fluidity of the hot melt adhesive, thereby improving the adhesion and buffering properties of the hot melt adhesive. In addition, the polymer containing maleic anhydride swells in the electrolyte, and under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the hot melt adhesive includes 30-40 parts by weight of a polymer containing maleic anhydride.
[0097] In some embodiments of the present application, the weight average molecular weight of the polymer containing maleic anhydride is 50,000-400,000. For example, the weight average molecular weight of the polymer containing maleic anhydride can be 50,000-350,000, 100,000-300,000, 150,000-250,000, 200,000-230,000, etc. Therefore, the use of the polymer containing maleic anhydride with a weight average molecular weight of the present application makes the hot melt adhesive have good adhesion to the pole piece, which can well buffer the pressure on the pole piece, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. In other embodiments of the present application, the weight average molecular weight of the polymer containing maleic anhydride is 100,000-200,000.
[0098] In some embodiments of the present application, the glass transition temperature of the polymer containing maleic anhydride is 50°C-100°C. For example, the glass transition temperature of the polymer containing maleic anhydride can be 50°C-95°C, 55°C-90°C, 60°C-85°C, 65°C-80°C, 70°C-75°C, etc. The glass transition temperature of the polymer containing maleic anhydride is within the above range, which will not affect the normal operation of the battery cell, and can improve the flexibility of the hot melt adhesive and the adhesion to the pole piece, reduce the probability of the hot melt adhesive separating from the pole piece, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. In other embodiments of the present application, the glass transition temperature of the polymer containing maleic anhydride is 50°C-70°C.
[0099] The glass transition temperature of the polymer containing maleic anhydride can be measured by the method commonly used in the art, for example, it can be tested by differential scanning calorimetry with reference to GB / T19466.2, with a heating rate of 10°C / min and an air atmosphere.
[0100] The method for determining the glass transition temperature of other substances hereinafter is the same as above.
[0101] In some embodiments of the present application, the maleic anhydride-containing polymer includes at least one of a maleic anhydride-containing butene-ethylene copolymer and a maleic anhydride-containing butene-octene copolymer. The maleic anhydride-containing polymer will not affect the normal operation of the battery cell, but can enhance the adhesion between the hot melt adhesive and the pole piece, improve the fluidity of the hot melt adhesive, and improve the adhesion and buffering performance of the hot melt adhesive. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece.
[0102] It can be understood that the butene-ethylene copolymer containing maleic anhydride is prepared by the following method: heating a three-necked flask and evacuating it, replacing the air in the flask with N2, adding a polyethylene base material and evacuating it at 80-100°C for 1 hour, adding ethylene / butene copolymer monomers pre-mixed in a gas mixing tank, and adding maleic anhydride to the three-necked flask, polymerizing at a constant pressure controlled by an electromagnetic valve for 2 hours, separating the solid, and obtaining a butene-ethylene copolymer containing maleic anhydride.
[0103] The butene-octene copolymer containing maleic anhydride is prepared by the following method: a reaction device is vacuumed and replaced with nitrogen three times repeatedly at 120° C. in advance, then butene is introduced, 23 mL of n-hexane and octene dehydrated and deoxygenated by reflux dehydration with metallic sodium are added to a reaction kettle (100 mL), and maleic anhydride is added, after the temperature of the reaction kettle drops to 60° C., a bridged bis-zirconocene catalyst is added under continuous stirring, the temperature is raised to the reaction temperature, and the reaction is carried out for 10-30 minutes under a certain butene pressure. After the reaction is completed, the polymerization solution is poured into acidified ethanol with a concentrated hydrochloric acid / ethanol volume ratio of 1:9 to terminate the reaction, and the polymerization product is obtained by washing with ethanol and vacuum drying.
[0104] In some embodiments of the present application, the hot melt adhesive includes 20-50 parts by weight of a toughening agent, for example, including 20-45 parts by weight of a toughening agent, 25-40 parts by weight of a toughening agent, 30-35 parts by weight of a toughening agent, etc. Therefore, the toughening agent of the content of the present application can swell after being soaked in the electrolyte, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell, and the toughening agent can improve the toughness of the hot melt adhesive, so that the buffering effect on the electrode pressure is obvious, and it plays a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the electrode. In other embodiments of the present application, the hot melt adhesive includes 30-40 parts by weight of a toughening agent.
[0105] In some embodiments of the present application, the weight average molecular weight of the toughening agent is 100,000-500,000. For example, the weight average molecular weight of the toughening agent is 100,000-450,000, 150,000-400,000, 200,000-350,000, 250,000-300,000, etc. Therefore, the toughening agent with a weight average molecular weight of the present application can swell after being soaked in the electrolyte, the spacing between the molecular chains increases, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains, which will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the weight average molecular weight of the toughening agent is 200,000-300,000.
[0106] In some embodiments of the present application, the glass transition temperature of the toughening agent is -50°C-50°C. For example, the glass transition temperature of the toughening agent can be -50°C-45°C, -45°C-40°C, -40°C-35°C, -35°C-30°C, -30°C-25°C, -25°C-20°C, -20°C-15°C, -15°C-10°C, -10°C-5°C, -5°C-0°C, etc. The glass transition temperature of the toughening agent of the present application is within the above range, which can improve the flexibility of the toughening agent, improve the adhesion of the hot melt adhesive, reduce the probability of the hot melt adhesive and the pole piece being separated, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. It can be selected as -20°C-50°C.
[0107] In some embodiments of the present application, the degree of branching of the toughening agent is 500-800, for example, the degree of branching of the toughening agent can be 500-750, 550-700, 600-650, etc. The degree of branching of the toughening agent is within the above range, and it can swell after being immersed in the electrolyte, the spacing between the molecular chains increases, and the active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains, which will not affect the operation of the battery cell, and can improve the toughness of the hot melt adhesive. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the degree of branching of the toughening agent is 500-700.
[0108] In some embodiments of the present application, the toughening agent includes at least one of styrene-isoprene-styrene triblock copolymer, styrene-butylene-styrene triblock copolymer and styrene-1-hexene-styrene triblock copolymer. The molecular chain segments of the toughening agent are soft, which can improve the flexibility of the hot melt adhesive, improve the pressure sensitivity of the hot melt adhesive, and absorb electrolyte to increase the swelling rate. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece.
[0109] It can be understood that the styrene-isoprene-styrene triblock copolymer is composed of three segments, polystyrene segment (S)-polyisoprene segment (I)-polystyrene segment (S), so it is called SIS; the styrene-butylene-styrene triblock copolymer is the styrene-butadiene-styrene block copolymer (SBS).
[0110] The styrene-1-hexene-styrene triblock copolymer was prepared by the following method: in a low-temperature glove box without water and oxygen, 30 mL of solvent (V (cyclohexane) / V (monochloromethane) = 1:1) was added to a dry polymerization bottle at -80°C, and after uniform mixing, a quantitative amount of 1,4-di(2-chloro-2-propyl)benzene, a proton scavenger (2,6-di-tert-butylpyridine), and titanium tetrachloride were added in sequence. After aging for 1 minute, the first monomer 1-hexene was added, and after reacting for 90 minutes, the second monomer styrene was added. After reacting for 3.5 hours, methanol was added to terminate the reaction. After removing the solvent from the product, it was vacuum dried at 35°C to constant mass.
[0111] In some embodiments of the present application, the hot melt adhesive includes 1-10 parts by weight of a tackifier. For example, the hot melt adhesive also includes 1-9 parts by weight of a tackifier, 2-8 parts by weight of a tackifier, 3-7 parts by weight of a tackifier, 4-6 parts by weight of a tackifier, etc. Specifically, the use of the tackifier content of the present application can increase the viscosity of the hot melt adhesive, reduce the probability of the hot melt adhesive falling off during the battery cycle, and play a good buffering role without affecting the normal operation of the battery cell, reducing the cracking of the pole piece. In other embodiments of the present application, the hot melt adhesive also includes 1-5 parts by weight of a tackifier.
[0112] In some embodiments of the present application, the weight average molecular weight of the tackifier is 10,000-100,000. For example, the weight average molecular weight of the tackifier can be 10,000-90,000, 20,000-80,000, 30,000-70,000, 40,000-60,000, etc. Specifically, within the weight average molecular weight range of the above tackifier, the viscosity of the hot melt adhesive can be improved, and the probability of the hot melt adhesive falling off during the battery cycle can be reduced. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the weight average molecular weight of the tackifier is 20,000-50,000.
[0113] In some embodiments of the present application, the glass transition temperature of the tackifier is 50°C-90°C. For example, the glass transition temperature of the tackifier can be 50°C-85°C, 55°C-80°C, 60°C-75°C, 65°C-70°C, etc. Within the glass transition temperature range of the above tackifier, the flexibility of the tackifier resin can be improved, the adhesion of the hot melt adhesive can be improved, and the probability of the hot melt adhesive falling off during the battery cycle can be reduced. Without affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the glass transition temperature of the tackifier is 60°C-70°C.
[0114] In some embodiments of the present application, the tackifier includes at least one of polyisobutylene, polyisoprene and butyl rubber. Thus, the tackifier can improve the viscosity of the hot melt adhesive, improve the bonding force between the hot melt adhesive and the pole piece, reduce the probability of the hot melt adhesive falling off during the battery cycle, and play a good buffering role and reduce the cracking of the pole piece without affecting the normal operation of the battery cell.
[0115] In some embodiments of the present application, polymers containing maleic anhydride, toughening agents and viscosity-enhancing adhesives are used as swelling components and can swell in the electrolyte. Active ions can freely shuttle and transport in the gaps between the hot melt adhesive molecular chains without affecting the operation of the battery cell. The toughness and strength of the hot melt adhesive can be improved, thereby playing a good buffering role and reducing the cracking of the electrode.
[0116] In some embodiments of the present application, the hot melt adhesive further comprises 0.1 to 1 parts by weight of additives, for example, the hot melt adhesive further comprises 0.1 to 0.9 parts by weight of additives, 0.2 to 0.8 parts by weight of additives, 0.3 to 0.7 parts by weight of additives, 0.4 to 0.6 parts by weight of additives, etc. In other embodiments of the present application, the hot melt adhesive further comprises 0.1 to 0.5 parts by weight of additives.
[0117] In some embodiments of the present application, the additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol and pentaerythritol tetrakis (3-laurylthiopropionate). Thus, the antioxidant performance of the hot melt adhesive can be improved and the life cycle of the hot melt adhesive can be extended.
[0118] The second aspect of the present application provides a method for preparing a hot melt adhesive, comprising: mixing a polyolefin, a polymer containing maleic anhydride, a toughening agent and a tackifying adhesive to obtain a hot melt adhesive, wherein the solubility rate of the hot melt adhesive in an organic solvent is less than or equal to 8%.
[0119] Therefore, the hot melt adhesive prepared by the method has good electrolyte resistance and good bonding performance with the electrode. When the hot melt adhesive is used on the electrode, the hot melt adhesive plays a buffering role when the electrode is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.
[0120] The third aspect of the present application provides an adhesive tape, comprising a substrate and an adhesive layer provided on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in the first aspect of the present application or the hot melt adhesive prepared by the method described in the second aspect of the present application.
[0121] In some specific embodiments, the material of the substrate can be the same as that of the separator of the battery, and any known porous structure separator with electrochemical stability and mechanical stability can be selected according to actual needs. For example, the substrate can be a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. In this way, the substrate has good electrolyte resistance, and the active ions can normally penetrate the holes on the surface of the substrate, which can provide certain protection for the pole piece without reducing the energy density of the battery.
[0122] In some specific embodiments, the thickness ratio of the adhesive layer to the substrate is (5-8): (9-13). For example, the thickness ratio of the adhesive layer to the substrate can be (5-7): (9-12), (6-7): (10-11), (5-6): (10-11), etc. The substrate can provide a certain buffering support for the electrode. The thickness ratio of the adhesive layer to the substrate is within the above range, which can well play the buffering role of the hot melt adhesive, enhance the buffering effect, and improve the wettability of the electrolyte. Without affecting the normal operation of the battery cell, it can play a good buffering role and reduce the cracking of the electrode. In other embodiments of the present application, the thickness ratio of the adhesive layer to the substrate is (7-8): (11-13).
[0123] In some embodiments of the present application, the thickness of the adhesive tape is 16μm-20μm, for example, the thickness of the adhesive tape can be 16μm-19μm, 17μm-19μm, 17μm-18μm, etc. The thickness of the adhesive tape within the above range can well play the buffering role of the hot melt adhesive, strengthen the buffering effect, and improve the wettability of the electrolyte. Under the premise of not affecting the normal operation of the battery cell, it plays a good buffering role and reduces the cracking of the pole piece. In other embodiments of the present application, the thickness of the adhesive tape is 16μm-18μm.
[0124] In some embodiments of the present application, the preparation method of the adhesive tape is as follows: hot melt adhesive is coated on a substrate to form an adhesive layer, and then a layer of release agent is coated on the side of the adhesive layer facing away from the substrate. The adhesive layer of the adhesive tape is attached to at least one side of the positive electrode sheet and / or the negative electrode sheet, and is in contact with the positive electrode sheet and / or the negative electrode sheet.
[0125] In some embodiments of the present application, the method for preparing the release agent is as follows: cobalt blue powder and phthalocyanine blue are stirred and dispersed in a polyurethane solution, and a solvent is added for dilution while stirring. The solvent can be at least one of toluene, ethyl acetate, and n-hexane. The stirring temperature can be 50°C-70°C, for example, the stirring temperature can be 50°C-65°C, 55°C-60°C, etc. The stirring time can be 30-60 minutes, for example, the stirring time can be 30 minutes-55 minutes, 35 minutes-50 minutes, 40 minutes-45 minutes, etc.
[0126] The fourth aspect of the present application provides a wound battery cell, comprising a positive electrode sheet, a separator and a negative electrode sheet stacked and wound in sequence, and the adhesive tape described in the third aspect of the present application is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator.
[0127] In some embodiments of the present application, reference Figure 1 The wound battery cell 10 includes: a positive electrode sheet 102, a separator 103 and a negative electrode sheet 101 which are stacked and wound in sequence, and the adhesive tape 106 is provided between the positive electrode sheet 102 and the separator 103 and / or between the negative electrode sheet 101 and the separator 103.
[0128] Adhesive tape 106 is arranged between the positive electrode sheet 102 and the isolation membrane 103 and / or between the negative electrode sheet 101 and the isolation membrane 103. The hot melt adhesive of the adhesive tape 106 has good electrolyte resistance and good bonding performance with the positive electrode sheet 102 and / or the negative electrode sheet 101. The adhesive tape 106 plays a buffering role when the positive electrode sheet 102 and / or the negative electrode sheet 101 is subjected to pressure, which can greatly improve the problem of electrode cracking and increase the life of the battery cell without affecting the normal operation of the wound battery cell 10.
[0129] In some embodiments of the present application, the adhesive layer of the adhesive tape 106 is attached to at least one side of the positive electrode plate 102 and is in contact with the positive electrode plate 102. The hot melt adhesive of the adhesive layer has good electrolyte resistance and good bonding performance with the electrode plate. The hot melt adhesive acts as a buffer when the electrode plate is subjected to pressure, which can greatly improve the problem of electrode plate cracking and increase the life of the battery cell without affecting the normal operation of the battery cell.
[0130] In some embodiments of the present application, reference Figure 1 and Figure 2 , Figure 2 It is a part of the positive electrode sheet. The positive electrode sheet 102 includes alternately arranged positive electrode sheet plane sections 102-2 and bent sections 102-1 of the positive electrode sheet. Correspondingly, the negative electrode sheet 101 also has a negative electrode sheet plane section and a bent section 101-1 of the negative electrode sheet. At least one side of the bent section 102-1 of the positive electrode sheet is provided with the adhesive tape 106. Therefore, the bent section 102-1 of the positive electrode sheet has an arc-shaped area, which is subjected to great force. The adhesive tape 106 is provided on at least one side of the bent section 102-1 of the positive electrode sheet, which can well improve the problem of electrode sheet cracking, increase the life of the battery cell, and will not affect the normal operation of the battery cell.
[0131] In some embodiments of the present application, the adhesive tape 106 is provided on at least one side of the bent section 102-1 of the positive electrode sheet near the center of the wound battery cell 10. Thus, the bent section 102-1 of the positive electrode sheet near the center of the wound battery cell 10 is subjected to great force and is prone to cracking. The adhesive tape 106 is provided on at least one side of the bend 104 of the positive electrode sheet near the center of the wound battery cell 10, which can improve the problem of sheet cracking and increase the life of the battery cell. The adhesive tape is provided exactly at the position where the sheet is prone to cracking, without any excess adhesive tape, and the active ion shuttle resistance of the wound battery cell is small and the energy density is high.
[0132] It can be understood that the “bent section of the positive electrode sheet close to the center of the wound battery cell” refers to the innermost circle of the positive electrode sheet of the wound battery cell.
[0133] In some embodiments of the present application, the adhesive tape 106 is provided on both sides of the bent section 102-1 of the positive electrode sheet near the center of the wound battery cell 10. In this way, the adhesive tape 106 relieves pressure from both sides, which can greatly improve the problem of sheet cracking and increase the life of the battery cell.
[0134] In some embodiments of the present application, the positive electrode plate includes a positive current collector, and the positive current collector can be a metal foil, a foam metal or a composite current collector. For example, as a metal foil, aluminum or stainless steel, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium with a silver surface treatment can be used. The composite current collector may include a polymer material base and a metal layer. The foam metal may be a nickel foam, a copper foam, an aluminum foam, a foam alloy, or a carbon foam. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0135] In some embodiments of the present application, the positive electrode plate may further include a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material. The specific type of the positive electrode active material is not limited, and active materials known in the art that can be used for battery positive electrodes can be used. Those skilled in the art can select according to actual needs.
[0136] As an example, the positive electrode active material may include, but is not limited to, at least one of lithium transition metal oxides, lithium-containing phosphates of olivine structure and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds. Examples of lithium-containing phosphates of olivine structure may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their modified compounds. These materials can all be obtained commercially.
[0137] In some embodiments of the present application, other functional layers may be provided between the positive electrode active material layer and the hot melt adhesive.
[0138] For example, when the battery is a sodium ion battery, as an example, the positive electrode active material may include but is not limited to at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue analog.
[0139] Examples of the layered transition metal oxides include:
[0140] Na 1-x Cu h Fe k Mn l M 1 m O 2-y , where M 1 is at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn and Ba, 0 <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2;
[0141] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 is at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn and Ba, 0 <z≤0.1;
[0142] Na a Li b Ni c Mn d Fe eO2, where 0.67 < a ≤ 1, 0 < b < 0.2, 0 < c < 0.3, 0.67 < d + e < 0.8, and b + c + d + e = 1.
[0143] Examples of the above polyanion compounds include, for example:
[0144] A 1 f M 3 g (PO4) i O j X 1 3-j , where A 1 is at least one of H, Li, Na, K, and NH4, M 3 is at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu, and Zn, X 1 is at least one of F, Cl, and Br, 0 < f ≤ 4, 0 < g ≤ 2, 1 ≤ i ≤ 3, 0 ≤ j ≤ 2;
[0145] Na n M 4 PO4X 2 , where M 4 is at least one of Mn, Fe, Co, Ni, Cu, and Zn, X 2 is at least one of F, Cl, and Br, 0 < n ≤ 2;
[0146] Na p M 5 q (SO4)3, where M 5 is at least one of Mn, Fe, Co, Ni, Cu, and Zn, 0 < p ≤ 2, 0 < q ≤ 2;
[0147] Na s Mn t Fe 3-t (PO4)2(P2O7), where 0 < s ≤ 4, 0 ≤ t ≤ 3, for example, t is 0, 1, 1.5, 2, or 3.
[0148] Examples of the above Prussian blue analogs include, for example:
[0149] A u M 6 v [M 7 (CN)6] w ·xH2O, where A is H + 、NH4 + 、alkali metal cations, and alkaline earth metal cations, M 6 and M7 Each independently represents at least one of transition metal cations, where 0 < u ≤ 2, 0 < v ≤ 1, 0 < w ≤ 1, and 0 < x < 6. For example, A is H + , Li + , Na + , K + , NH4 + , Rb + , Cs + , Fr + , Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Ra 2+ at least one of, M 6 and M 7 Each independently represents a cation of at least one transition metal element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn, and W.
[0150] The modified compounds of the above materials can be doping modification and / or surface coating modification of the materials.
[0151] The positive electrode active material layer usually also optionally includes a binder, a conductive agent, and other optional additives.
[0152] As an example, the conductive agent can include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, SuperP (SP), graphene, and carbon nanofibers.
[0153] As an example, the binder can include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB).
[0154] In some embodiments of the present application, the negative electrode plate includes a negative electrode current collector, and the negative electrode current collector can be a metal foil, a foam metal or a composite current collector. For example, as a metal foil, aluminum or stainless steel treated with silver surface, stainless steel, copper, aluminum, nickel, carbon electrode, carbon, nickel or titanium, etc. can be used. The foam metal can be foam nickel, foam copper, foam aluminum, foam alloy, or foam carbon, etc. The composite current collector may include a polymer material base layer and a metal layer, and the composite current collector may be formed by placing a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0155] In some embodiments of the present application, the negative electrode plate may further include a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material. The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for battery negative electrodes can be used. Those skilled in the art can select according to actual needs.
[0156] As an example, the negative electrode active material may include but is not limited to at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. The silicon-based material may include at least one of elemental silicon, silicon oxide (e.g., silicon monoxide), silicon-carbon composite, silicon-nitrogen composite, and silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy. These materials can all be obtained commercially.
[0157] In some embodiments of the present application, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0158] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.
[0159] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0160] As an example, the adhesive may include at least one of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB).
[0161] As examples, other optional additives may include thickeners and dispersants (eg, sodium carboxymethyl cellulose CMC-Na), and PTC thermistor materials.
[0162] In some embodiments of the present application, as the above-mentioned isolation membrane, the present application has no particular restrictions, and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can be a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0163] In some embodiments of the present application, the wound battery cell may further include an electrolyte, and the electrolyte may include an electrolyte salt and a solvent.
[0164] As an example, when the battery is a lithium ion battery, the electrolyte lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0165] As an example, when the battery is a sodium ion battery, the electrolyte sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide.
[0166] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0167] In some embodiments of the present application, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0168] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 3 The secondary battery 1 is a square structure as an example.
[0169] The fifth aspect of the present application provides a battery, comprising the wound battery cell described in the fourth aspect of the present application, so that the battery has a longer life.
[0170] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0171] In some embodiments of the present application, the battery 1 may include an outer package for packaging the positive electrode sheet, the negative electrode sheet and the electrolyte.
[0172] In some embodiments of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0173] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly. The number of electrode assemblies contained in the battery can be one or more, which can be adjusted according to demand.
[0174] In some embodiments of the present application, the outer packaging of the battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0175] The outer packaging of the battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0176] In some embodiments of the present application, the batteries may be assembled into a battery module. The battery module may contain multiple sodium-ion batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0177] Figure 4 2 is an example of a battery module 2. Figure 4 In the battery module 2, the plurality of secondary batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 1 may be fixed by fasteners.
[0178] The battery module 2 may also include a housing having a storage space, in which a plurality of secondary batteries 1 are stored. In some embodiments of the present application, the battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0179] Figure 5 and 6 The battery pack 3 is used as an example. Figure 5 and 6 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0180] The sixth aspect of the present application provides an electrical device, comprising the battery described in the fifth aspect of the present application. Thus, the electrical device has a long life cycle.
[0181] As an example, the power-consuming device includes at least one of the battery, battery module and battery pack. The battery, battery module or battery pack can be used as a power source for the power-consuming device, or as an energy storage unit for the power-consuming device. The power-consuming device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck), an electric train, a ship and a satellite, and an energy storage system.
[0182] The electrical equipment may select the secondary battery 1 , the battery module 2 or the battery pack 3 according to its usage requirements.
[0183] Figure 7 The power consumption device is used as an example. The power consumption device includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the battery, a battery pack or a battery module can be used.
[0184] As another example, the electric device may include a mobile phone, a tablet computer, and a notebook computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0185] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0186] Example 1
[0187] 1. Preparation of hot melt adhesive
[0188] The polyolefin, the polymer containing maleic anhydride, the toughening agent, the tackifying adhesive and the additive were mixed, first stirred at 1200 rpm for 60 min, then stirred at 800 rpm for 90 min to make the components evenly mixed, and finally filled and discharged to obtain the hot melt adhesive.
[0189] 2. Preparation of adhesive tape
[0190] The hot melt adhesive is coated on the polyethylene film to form an adhesive layer to obtain adhesive paper.
[0191] 3. Preparation of positive electrode
[0192] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.2:2.7:1.1 to obtain positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and cutting processes, and adhesive tape is adhered to the bent section of the positive electrode sheet close to the center of the wound battery cell.
[0193] 4. Preparation of negative electrode
[0194] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0195] 5. The isolation film is made of polyethylene film.
[0196] 6. Preparation of electrolyte
[0197] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried electrolyte salt LiPF6 is dissolved in the organic solvent, the concentration of the electrolyte salt is 1.0 mol / L, and the mixture is evenly mixed to obtain an electrolyte solution.
[0198] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected into the dried battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0199] The hot melt adhesives of Examples 2-66 and Comparative Examples 1-4 are the same as Example 1 except for the different parameters (see Table 1).
[0200] Table 1
[0201]
[0202]
[0203]
[0204]
[0205]
[0206] In Table 1, A represents a butene-ethylene copolymer containing maleic anhydride, B represents a butene-octene copolymer containing maleic anhydride, A and B belong to polymers containing maleic anhydride, C represents a styrene-isoprene-styrene triblock copolymer, D represents a styrene-butylene-styrene triblock copolymer, and E represents a styrene-1-hexene-styrene triblock copolymer, and C, D and E belong to toughening agents.
[0207] The positive electrode plate coated with hot melt adhesive was immersed in the above electrolyte, and the bonding strength between the hot melt adhesive and the current collector was tested before immersion, 1 day, 4 days and 7 days, and the dissolution rate and swelling rate of the hot melt adhesive in the electrolyte were measured. The test results are shown in Table 2.
[0208] Test method:
[0209] 1. Adhesion test before immersion:
[0210] Cut the sample into a size of 20*100mm for later use; take a stainless steel plate with a clean surface, wipe both sides of the plate with alcohol, then stick the cut sample horizontally on the surface of the stainless steel plate, and roll it horizontally with a 2kg roller for 2 circles to make the adhesive tape and the steel plate fit tightly; bend one end of the sample in the opposite direction with a bending angle of 180°; use a high-speed rail tensile testing machine to test, fix one end of the stainless steel to the clamp below the tensile testing machine, and fix the bent end of the sample to the upper clamp, adjust the angle of the sample to ensure that the upper and lower ends are in a vertical position, and then stretch the sample at a speed of 50mm / min until the sample is completely peeled off from the substrate, and record the displacement and force in the process. It is generally believed that the force when the force is balanced is the bonding force of the sample.
[0211] 2. Adhesion test after immersion in electrolyte:
[0212] Cut the sample into a size of 20*100mm for later use; take a stainless steel plate with a clean surface, wipe both sides of the plate with alcohol, then stick the cut sample horizontally on the surface of the stainless steel plate, and roll it horizontally with a 2kg roller for 2 circles to make the adhesive tape and the steel plate fit tightly; put the sample into an aluminum box filled with electrolyte, seal it with tin foil and put it into a forced air drying oven, set the temperature to 70℃, take out the samples after soaking for 1 day, 4 days and 7 days respectively, wipe the electrolyte on the surface of the glue with dust-free paper, and start the adhesion test after standing in the air for 10 minutes, using the same method as the adhesion test before soaking in 1.
[0213] 3. Swelling rate test:
[0214] Preparation of adhesive film: Take a certain amount of prepared hot melt adhesive and put it into a blast drying oven, set it to 70℃ and dry it for 24 hours to completely evaporate the solvent to make an adhesive film with a solid content of 100%;
[0215] 1) Weigh a certain mass of film, record it as M3
[0216] 2) Immerse in electrolyte at 70°C for 5 hours;
[0217] 3) Take out the hot melt adhesive and wipe the surface of the hot melt adhesive dry with dust-free paper;
[0218] 4) After standing for 20 minutes, weigh it and record it as M4
[0219] 5) Calculate the swelling ratio = (M4-M3) x 100% / M3.
[0220] 4. Dissolution rate test:
[0221] 1) Weigh a certain mass of film, record it as M1
[0222] 2) Immerse in electrolyte at 70°C for 5 hours;
[0223] 3) Take out the membrane and wipe off the solvent on the surface of the membrane with dust-free paper;
[0224] 4) Place the film in an oven and dry at 90°C for 24 hours;
[0225] 5) Take out the membrane and wipe the solvent off the surface of the membrane with dust-free paper.
[0226] 6) Place the film in an oven at 90°C and dry for 24 hours.
[0227] 7) Take out the membrane and weigh it, record it as M2
[0228] 8) Calculate the dissolution rate = (M1-M2) × 100% / M1
[0229] Table 2
[0230]
[0231]
[0232]
[0233] As can be seen from Table 2, the four components of the hot melt adhesive of Examples 1-66 of the present application work together, so that the hot melt adhesive has a low dissolution rate in the electrolyte, a small change in adhesion after soaking in the electrolyte, good electrolyte resistance, and swelling after soaking in the electrolyte, so that the spacing between the hot melt adhesive molecular chains increases, and active ions can freely shuttle and transmit in the gaps between the hot melt adhesive molecular chains. That is, the hot melt adhesive will not affect the normal operation of the wound battery cell, and can play a buffering role to improve the cracking of the pole piece.
[0234] The dissolution rate of the hot melt adhesive in comparative example 1 in the organic solvent is not within the range of the embodiments of the present application. Comparative examples 2, 3 and 4 lack a component, and their electrolyte resistance and adhesion are far lower than those of the embodiments of the present application.
[0235] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A hot melt adhesive, characterized in that: include: Polyolefin, polymer containing maleic anhydride, toughening agent and tackifying adhesive, wherein the dissolution rate of the hot melt adhesive in an organic solvent is less than or equal to 8%.
2. The hot melt adhesive according to claim 1, characterized in that: The hot melt adhesive comprises 10-60 parts by weight of polyolefin, 20-50 parts by weight of polymer containing maleic anhydride, 20-50 parts by weight of toughening agent and 1-10 parts by weight of tackifying adhesive. Optionally, the hot melt adhesive comprises 10-40 parts by weight of polyolefin, 30-40 parts by weight of polymer containing maleic anhydride, 30-40 parts by weight of toughening agent and 1-5 parts by weight of tackifying adhesive.
3. The hot melt adhesive according to claim 1 or 2, characterized in that: The dissolution rate of the hot melt adhesive in the organic solvent is 4%-7%, and can be optionally 5%-6%.
4. The hot melt adhesive according to any one of claims 1 to 3, characterized in that: The solubility parameter of the polyolefin is 9 cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 , optional 10cal 1 / 2 / cm 3 / 2 -11cal 1 / 2 / cm 3 / 2 .
5. The hot melt adhesive according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the polyolefin is 100,000-400,000, and can be optionally 200,000-300,000.
6. The hot melt adhesive according to any one of claims 1 to 5, characterized in that: The melting point of the polyolefin is 140°C-160°C, and can be optionally 145°C-155°C.
7. The hot melt adhesive according to any one of claims 1 to 6, characterized in that: The crystallinity of the polyolefin is 1%-30%, and can be optionally 10%-20%.
8. The hot melt adhesive according to any one of claims 1 to 7, characterized in that: The polyolefin includes at least one of polypropylene, cycloolefin polymer and hexene octene copolymer.
9. The hot melt adhesive according to any one of claims 1 to 8, characterized in that: The weight average molecular weight of the maleic anhydride-containing polymer is 50,000-400,000, and can be 100,000-200,000.
10. The hot melt adhesive according to any one of claims 1 to 9, characterized in that: The glass transition temperature of the maleic anhydride-containing polymer is 50°C-100°C, and can be optionally 50°C-70°C.
11. The hot melt adhesive according to any one of claims 1 to 10, characterized in that: The maleic anhydride-containing polymer includes at least one of a maleic anhydride-containing butene-ethylene copolymer and a maleic anhydride-containing butene-octene copolymer.
12. The hot melt adhesive according to any one of claims 1 to 11, characterized in that: The weight average molecular weight of the toughening agent is 100,000-500,000, and can be optionally 200,000-300,000.
13. The hot melt adhesive according to any one of claims 1 to 12, characterized in that: The glass transition temperature of the toughening agent is -50°C-50°C, and can be optionally -20°C-50°C.
14. The hot melt adhesive according to any one of claims 1 to 13, characterized in that: The branching degree of the toughening agent is 500-800, and can be optionally 500-700.
15. The hot melt adhesive according to any one of claims 1 to 14, characterized in that: The toughening agent includes at least one of styrene-isoprene-styrene triblock copolymer, styrene-butylene-styrene triblock copolymer and styrene-1-hexene-styrene triblock copolymer.
16. The hot melt adhesive according to any one of claims 1 to 15, characterized in that: The weight average molecular weight of the tackifier is 10,000-100,000, and can be optionally 20,000-50,000.
17. The hot melt adhesive according to any one of claims 1 to 16, characterized in that: The glass transition temperature of the tackifier adhesive is 50°C-90°C, and can be 60°C-70°C.
18. The hot melt adhesive according to claims 1-17, characterized in that: The tackifier rubber includes at least one of polyisobutylene, polyisoprene and butyl rubber.
19. The hot melt adhesive according to any one of claims 1 to 18, characterized in that: The hot melt adhesive further comprises 0.1 to 1 parts by weight of an additive, and optionally, further comprises 0.1 to 0.5 parts by weight of an additive.
20. The hot melt adhesive according to claim 19, characterized in that: The additive includes at least one of N-phenyl-β-naphthylamine, 2,6-di-tert-butyl-p-cresol, 3-methyl-6-tert-butylphenol and pentaerythritol tetrakis (3-laurylthiopropionate).
21. A method for preparing the hot melt adhesive according to any one of claims 1 to 20, characterized in that: include: The polyolefin, the polymer containing maleic anhydride, the toughening agent and the viscosity enhancing adhesive are mixed to obtain the hot melt adhesive, wherein the dissolution rate of the hot melt adhesive in the organic solvent is less than or equal to 8%.
22. A tape, characterized in that: It comprises a substrate and an adhesive layer arranged on at least one side of the substrate, wherein the adhesive layer comprises the hot melt adhesive described in any one of claims 1 to 20 or the hot melt adhesive prepared by the method described in claim 21.
23. The adhesive tape according to claim 22, characterized in that: The adhesive tape meets at least one of the following conditions: The thickness ratio of the adhesive layer to the substrate is (5-8):(9-13), and can be optionally (7-8):(11-13); The thickness of the adhesive tape is 16 μm-20 μm, and can be optionally 16 μm-18 μm.
24. A wound battery cell, characterized in that: It comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound in sequence, and the adhesive tape according to claim 22 or 23 is provided between the positive electrode sheet and the separator and / or between the negative electrode sheet and the separator.
25. The wound battery cell according to claim 24, characterized in that: The positive electrode plate comprises planar sections and bent sections which are arranged alternately, and the adhesive tape is disposed on at least one side of the bent section.
26. The wound battery cell according to claim 25, characterized in that: The adhesive tape is arranged on at least one side of the bending section close to the center of the wound battery core.
27. A battery, characterized in that: A wound battery cell comprising any one of claims 24-26.
28. An electrical equipment, characterized in that: Comprising the battery of claim 27.
Citation Information
Patent Citations
Hot melt adhesive with rapid adhesive property and preparation method thereof
CN114350282A
Electrolyte-resistant double-sided multi-layer adhesive tape with ultrathin base material and preparation method
CN115710474A
Adhesive tape, and electrochemical device and electronic device comprising same
WO2023044862A1
